2016
DOI: 10.1080/15384101.2016.1160985
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitochondrial unfolded protein response by acetylcholine alleviated hypoxia/reoxygenation-induced apoptosis of endothelial cells

Abstract: The mitochondrial unfolded protein response (UPR(mt)) is involved in numerous diseases that have the common feature of mitochondrial dysfunction. However, its pathophysiological relevance in the context of hypoxia/reoxygenation (H/R) in endothelial cells remains elusive. Previous studies have demonstrated that acetylcholine (ACh) protects against cardiomyocyte injury by suppressing generation of mitochondrial reactive oxygen species (mtROS). This study aimed to explore the role of UPR(mt) in endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Interestingly, more recent work in cultured cell models of hypoxia/reoxygenation injury supports beneficial effects of acetylcholine on autophagy [150], and mitochondrial biogenesis [151] and quality control via mitophagy [152]. Similarly, vagal nerve stimulation may limit myocardial injury by inhibiting mitochondrial dysfunction and associated apoptosis [139], though this study found protection was limited to intra-ischemic intervention while post-ischemic stimulation was Additionally, M3 agonism with choline is cardioprotective [146,156], and the M3 receptor is implicated in the anti-apoptotic effects of acetylcholine [154] and in vagally mediated protection [133]. Finally, nicotinic receptors may also participate, with the study of Calvillo et al supporting involvement of the nicotinic pathway and inflammatory modulation in cardioprotection via vagal stimulation [137].…”
Section: Vagal Dysfunctionmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, more recent work in cultured cell models of hypoxia/reoxygenation injury supports beneficial effects of acetylcholine on autophagy [150], and mitochondrial biogenesis [151] and quality control via mitophagy [152]. Similarly, vagal nerve stimulation may limit myocardial injury by inhibiting mitochondrial dysfunction and associated apoptosis [139], though this study found protection was limited to intra-ischemic intervention while post-ischemic stimulation was Additionally, M3 agonism with choline is cardioprotective [146,156], and the M3 receptor is implicated in the anti-apoptotic effects of acetylcholine [154] and in vagally mediated protection [133]. Finally, nicotinic receptors may also participate, with the study of Calvillo et al supporting involvement of the nicotinic pathway and inflammatory modulation in cardioprotection via vagal stimulation [137].…”
Section: Vagal Dysfunctionmentioning
confidence: 67%
“…Other work supports vagal control of mitochondrial dynamics, likely promoting stresstolerance and limiting cell death[153]. Inhibition of the mitochondrial unfolded protein response may additionally contribute to anti-apoptotic effects of acetylcholine, potentially via inhibition of mitochondrial oxidant generation[154]. Studies thus collectively reveal important roles for vagal activity in dynamic maintenance of mitochondrial phenotype and function.…”
mentioning
confidence: 91%
“…Little information about the impact of URPmt is described in the context of heart diseases. Acute ischemia/hypoxia-reperfusion induces UPRmt in C. elegans [39] or endothelial cells [40] and can be a protective response. However, loss of the mitochondrial aspartyl tRNA-synthetase encoding gene DARS2 in mice results in dysregulation of mitochondrial translation and strong cardiomyopathy associated with an increase of UPRmt markers [41].…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…Studies in our laboratory have demonstrated that ACh prevents angiotensin II-induced cardiomyocyte injury through down-regulation of the angiotensin II type 1 receptor and inhibition of ROS-mediated p38 MAPK activation, as well as regulation of Bcl-2, Bax, and caspase-3 expression [ 48 , 79 81 ]. Recently, we demonstrated that ACh markedly suppresses the mitochondrial unfolded protein response and endoplasmic reticulum stress, which alleviate I/R injury [ 82 , 83 ]. ACh may also modulate the abnormal inter-organelle crosstalk in cardiovascular diseases.…”
Section: Cholinergic Drugs Used In the Treatment Of Cardiovascular DImentioning
confidence: 99%